Second language research : methodology and design - Mackey, Alison; Gass, Susan M. (New York : Routledge, 2016)
"This book is designed to be used as a text for introductory courses on research methodology and design, as well as for other courses in second language studies, where the emphasis is on research"
1. Introduction to research -- 2. Issues related to data gathering -- 3. Common data collection measures -- 4. Coding -- 5. Research variables, validity, and reliability -- 6. Designing a quantitative study -- 7. Qualitative research -- 8. Classroom research -- 9. Mixed methods -- 10. Analyzing quantitative data -- 11. Concluding and reporting research
Previous edition: Second language research
Includes bibliographical references (pages 405-424) and index
Keywords: Second language acquisition; Second language acquisition -- Research -- Methodology